Evidence for the evolution, clonal expansion and global dissemination of water treatment-resistant naturalized strains of Escherichia coli in wastewater. (1st June 2019) - Zhi, Shuai; Banting, Graham; Stothard, Paul; Ashbolt, Nicholas J.; Checkley, Sylvia; Meyer, Kelsey; Otto, Simon; Neumann, Norman F.
Abstract: We previously demonstrated the existence of naturalized strains of E. coli in wastewater and herein perform an in-depth comparative whole genome analysis of these strains (n = 17). Fourteen of the Canadian E. coli strains, isolated from geographically separated wastewater treatment plants, were virtually identical at the core genome and were ≥96% similar at the whole genome level, suggesting clonal-relatedness among these isolates. Remarkably, these strains were shown to be extremely similar to the genome of an E. coli isolated from wastewater in Switzerland, suggesting a global distribution of these strains. The genomes of three other Canadian wastewater strains were more diverse but very similar to the genomes of E. coli isolates collected from U.S. wastewater samples. Based on maximum likelihood phylogenetic analysis, wastewater strains from Canada, the U.S. and Switzerland formed a clade separate from other known enteric phylogroups (i.e., A, B1, B2, D, E) and the cryptic clades. All Canadian, Swiss and U.S. wastewater strains possessed a common SNP biomarker pattern across their genomes, and a sub-population (i.e., 14 Canadian and 1 Swiss strain) also possessed a previously identified wastewater-specific marker known as uspC-IS30-flhDC element. Biochemical heat mapping of 518 categories of genes recapitulated phylogeny, with wastewater strains phenotypically clustering separately from enteric and cryptic clades. Wastewater strains were enriched for stress-response genes (i.e., nutrient acquisition/deprivation, DNA repair, oxidative stress, and UV resistance) - elements reflective of their environmental survival challenges. Wastewater strains were shown to carry a plethora of known antibiotic resistance (AR) genes, the patterns of which were remarkably similar among all Canadian, U.S. and Swiss wastewater strains. Virulence gene composition was also similar among all the wastewater strains, with an abundant representation of virulence genes commonly associated with urinary pathogenic E. coli (UPEC) as well as enterohemorrhagic (EHEC) E. coli . The remarkable degree of similarity between all wastewater strains from Canada, Switzerland and the U.S. suggests the evolution and global-dissemination of water treatment-resistant clone of E. coli . These finding, along with others, raise some important concerns about the potential for emergence of E. coli pathotypes resistant to water-treatment. Graphical abstract: Image 1 Highlights: Naturalized wastewater strains of E. coli share a common genetic background. Naturalized wastewater strains are globally-distributed (Canada, U.S., and Switzerland). The genomes of wastewater strains of E. coli are enriched in stress-response elements. Wastewater strains share virulence and antibiotic resistance genes with enteric pathotypes. The data raises concerns about the emergence of water treatment-resistant pathotypes of E. coli .